1993
DOI: 10.3354/meps093165
|View full text |Cite
|
Sign up to set email alerts
|

Local and geographic variation in the defensive chemistry of a West Indian gorgonian coral (Briareum asbestinum)

Abstract: We sampled the between-colony and between-habitat variation in defensive chemistry of colonies of Briareum asbestinum, one of the most ubiquitous and chemically deterrent of the West Indian gorgonians. The basis of deterrence appears to reside in a diverse complement of 5 to 15 briarane and asbestinane diterpenoids found in individual colonies. Variation in chemistry of colonies is extensive throughout the Bahamas and the Virgin Islands: the complement of compounds is slightly different a t each site in the Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
66
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 22 publications
5
66
0
Order By: Relevance
“…273 Moreover, the larvae of this species synthesize the asbestinane diterpenes. 279 Similarly, pukalide 72 and 11 P-acetoxypukalide 73 were found in the eggs of the Pacific soft coral Sinularia polydactyla.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…273 Moreover, the larvae of this species synthesize the asbestinane diterpenes. 279 Similarly, pukalide 72 and 11 P-acetoxypukalide 73 were found in the eggs of the Pacific soft coral Sinularia polydactyla.…”
mentioning
confidence: 99%
“…300 A geographic comparison of colonies of the gorgonian Briareum asbestinum from two regions within the Caribbean, the Bahamas and St. Croix, showed that the two chemically defended populations produced different classes of diterpenes. 273 More recently, a study of the defenses of Annella mollis, A. reticulata and Rumphella sp. addressed geographic differences in the palatability of crude extracts of colonies collected from two distant tropical islands in the Pacific Ocean, Guam and Lizard Island, Australia.…”
mentioning
confidence: 99%
“…Hay and Steinberg [50] suggested that species (e.g., coral and algae) subjected to high feeding pressures have larger concentrations of metabolites against herbivory than others in less pressured environments, which may be an evolutionary consequence of self preservation. Secondly, a species with a slower growth rate might generate a surplus of natural products [48]. Thirdly, similar species living in different geographical locations may be ingesting different prey items, leading to differences in the concentration and type of metabolite produced.…”
Section: Hypothesis 1: Paragorgia Arborea From Various Geographic Regmentioning
confidence: 99%
“…Maida et al [47] reported significant differences in flexibilide and sinulariolide metabolites of the soft coral Sinularia flexibilis among different sites at Lizard Island, Great Barrier Reef (Australia). Metabolite concentrations varied among the gorgonian coral Briareum asbestimum from different depths and geographical locations [48].…”
Section: Hypothesis 1: Paragorgia Arborea From Various Geographic Regmentioning
confidence: 99%
“…temperature, light) and biological (e.g. life history, competition, size) variables (Harvell et al 1993, Becerro et al 1997, Maréchal et al 2004). The sterol composition of sea stars, such as Asterias rubens, can also be influenced by food availability, since most of the sterols are derived from the diet and only a few sterols are synthesized de novo (Voogt & Van Rheenen 1976).…”
Section: Hexadecanoic Cholesterol Lathosterol Sitosterol Acidmentioning
confidence: 99%